Outdoor education in Maria Montessori's philosophy: a chance for inclusion? - Barbara Caprara; Vanessa Macchia (Pensa MultiMedia, 2020)
In this paper, we are going to present some of the revolutionary and brilliant proposals of Maria Montessori's educational approach, which, through its innovative use of space and movement still offers solutions to problems in our day and age. Montessori's ideas are explained in relation to environmental education in the context of child-nature interaction as well as the practices applied within the framework of these ideas; they are also essential to facilitate educational inclusion, as they promote a sensory based and a child centered learning approach.